2011
DOI: 10.1108/17465721111175047
|View full text |Cite
|
Sign up to set email alerts
|

School‐based mental health service for refugee and asylum seeking children: multi‐agency working, lessons for good practice

Abstract: PurposeFollowing a description of the Haven Project: a school based Child and Adolescent Mental Health Service (CAMHS) for refugee children in Liverpool, this paper aims to raise awareness of a multiagency model for replication across community mental health services.Design/methodology/approachUsing semi‐structured interviews with school head teachers and outcome measures of group therapeutic sessions, a short service review has been conducted, set against background literature, identifying refugee statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Single interventions described for community-based mental health services pertained to the training of (future) healthcare workers and cultural brokering [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Resultsmentioning
confidence: 99%
“…Single interventions described for community-based mental health services pertained to the training of (future) healthcare workers and cultural brokering [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Resultsmentioning
confidence: 99%
“…Full-text articles excluded (n = 7), reasons: -assessing attitudes of minorities/refugees about access to healthcare and early psychosis intervention in NHS (n=3) -inquiry approach for mental health service provision with NGOs, RCOs Chaudhry et al, 2009;Chiumento et al, 2011Dora-Vila et al, 2012Fazel et al, 2009Amani 2012Edge & Grey 2018;Fazel et al, 2016;Hughes 2014;O'Shaughnessy et al, 2012 Targeted study sample Black, Asian, Minority Ethnics (BAME), settled in the UK 8 Afuwepe et al, 2010;Amani 2012;Chaudhry et al, 2009;Edge & Grey 2018;Hughes 2014;Rathod et al, 2013;Masood et al, 2015 BAME, refugees and asylum seekers with uncertain residency status 5 Chiumento et al, 2011;Dora-Vila et al, 2012;Fazel et al, 2009;Fazel et al, 2016;O'Shaughnessy et al, Chiumento et al, 2011;Dura-Vila et al, 2012;Fazel et al, 2009; Amani 2012…”
Section: Concluding Remarks and Implications For Researchmentioning
confidence: 99%
“…Dura-Villa et al, 2012Hughes 2014O'Shaughnessy et al, 2012Chiumento et al, 2011Fazel et al, 2009Fazel et al, 2016 *Single blind multi-site RCT **the study design is an exploratory RCT and has reported qualitative findings and a summary of the quantitative results in the intervention arm ***Masood et al, (2015) study was conducted in Manchester and Lancashire -At the end of study, refugee children continued to have significantly higher SDQ total (p = 0.011), emotional symptom (p < 0.001) and peer problem (p = 0.002) scores.…”
Section: Concluding Remarks and Implications For Researchmentioning
confidence: 99%
“…Having interventions based in schools can help to overcome some of the barriers to help-seeking for mental health concerns, such as lack of knowledge of appropriate services, lack of knowledge of referral pathways and stigma (Chiumento et al, 2011). School interventions may be universal, selective or targeted, and may address preventative, early intervention or responsive provision of mental health support to young people (Wells et al, 2003;Habib, 2012).…”
Section: Framing the Research Projectmentioning
confidence: 99%